2004
DOI: 10.1007/s00213-004-1782-1
|View full text |Cite
|
Sign up to set email alerts
|

FAUC 213, a highly selective dopamine D4 receptor full antagonist, exhibits atypical antipsychotic properties in behavioural and neurochemical models of schizophrenia

Abstract: Rationale: 2-[4-(4-Chlorophenyl)piperazin-1-ylmethyl]pyrazolo [1,5-a]pyridine (FAUC 213) is a highly selective antagonist at the dopamine D 4 receptor subtype. It was designed as a derivative of two partial antagonists and has been proven to be a complete antagonist in mitogenesis assay. Objectives: In the present study, FAUC 213 was examined for antipsychotic properties in animal models of behavioural neurobiology and neurochemistry. Methods: Different concentrations of FAUC 213 were screened for effects on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Visiers et al (2002) and Ebersole et al (2003) have already demonstrated that such differential positioning can lead to different functional phenotypes. Our discriminant findings should have clinical relevance as well, because the D4 dopamine receptor has been implicated in the treatment of a broad range of medical conditions, including attention deficit hyperactivity disorder (Avale et al, 2004), substance abuse (Lusher et al, 2001), neurodegeneration (Ishige et al, 2001), and psychosis (Boeckler et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Visiers et al (2002) and Ebersole et al (2003) have already demonstrated that such differential positioning can lead to different functional phenotypes. Our discriminant findings should have clinical relevance as well, because the D4 dopamine receptor has been implicated in the treatment of a broad range of medical conditions, including attention deficit hyperactivity disorder (Avale et al, 2004), substance abuse (Lusher et al, 2001), neurodegeneration (Ishige et al, 2001), and psychosis (Boeckler et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The assignment of the 2Ј-substituted diazole FAUC213 as a "neutral antagonist" using different measures of functional activity (fluorometric imaging plate reader G␣ qo5 -based versus mitogenesis-based) has been discussed recently (Stewart et al, 2004). It is remarkable that the D4-selective neutral antagonist FAUC213 was recently shown to have atypical antipsychotic potential in animal models predictive of antipsychotic efficacy in humans (Boeckler et al, 2004), in contrast to the structurally distinct D4-selective neutral antagonist PNU101,387G (sonepiprazole), which has no demonstrable antipsychotic activity in humans (Corrigan et al, 2004). It was previously demonstrated that the D4/D2 pharmacological selectivity profile of L745,870 and its differentially halogenated congener L750,667 become more like the substituted receptor when the corresponding amino acids present in the rat D2 subtype are substituted into a rat D4 receptor background (i.e., D4-F2.61V and D4-LM3.28-3.29FV mutants;Schetz et al, 2000) and when some of these and other reciprocal mutations are made in an N-and C-terminally epitope-tagged human D2 receptor background .…”
Section: Abbreviationsmentioning
confidence: 99%
“…Ropinirole is a preferential D 3/2 agonist (Gerlach et al 2003) with a 20-fold selectivity for D 3 over D 2 receptors (Reavill et al 2000), but it also has affinity for the DRD 4 subtype (Newman-Tancredi et al 2002). The DRD 4 subtype may also play a role in PPI modulation, as selective D 4 antagonists restore amphetamine-induced PPI deficits in mice (Mansbach et al 1998;Okuyama et al 1999;Boeckler et al 2004), although negative results have also been reported (Bristow et al 1997). While administration of agents that facilitate DA neurotransmission reliably disrupts PPI in animal studies (Mansbach et al 1988;Swerdlow et al 1998Swerdlow et al , 2001Swerdlow et al , 2002Swerdlow et al , 2003Geyer et al 2001), results in humans seem to depend on study design and baseline PPI at pretest (Bitsios et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Today, seven types of dopaminergic receptors are counted. Because of the large structural variety of heteroarenes, specific ligands of the dopaminergic receptor D3 [126,127] and selective modulators of the dopaminergic receptor D4 were developed [128,129]. New ferrocenyl carboxamides have shown a good affinity for these receptors and also, for serotoninergic receptors from the central nervous system.…”
Section: Dopaminergic Receptors Ligandsmentioning
confidence: 99%